2010
DOI: 10.2298/sos1003363p
|View full text |Cite
|
Sign up to set email alerts
|

Densification, microstructure and properties of supersolidus liquid phase sintered 6711Al-SiC metal matrix composites

Abstract: The present study compares the effect of SiC reinforcement on densification and properties of supersolidus liquid phase sintered 6711Al-SiC composites. The prealloyed 6711 powders were mixed with SiC ranging from 5 to 20 vol.%, compacted at 400 MPa and sintered at 630ºC under vacuum. It was shown that better densification, yield strength, wear and corrosion resistance were achieved up to 10 vol.% due to uniform distribution of SiC particles throughout matrix. Beyond 10 vol.%, SiC resulted in clustering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 47 publications
1
13
0
6
Order By: Relevance
“…The literature describes that press-sintering process is only a feasible technique if a low GNPs content is used in the composite. Otherwise, consolidation during sintering will be challenging [82,83]. For MMNCs with GNP content higher than 4 vol %, to reach full densification, an external pressure assisted method should be used.…”
Section: Consolidation and Sintering (Third Challenge)mentioning
confidence: 99%
“…The literature describes that press-sintering process is only a feasible technique if a low GNPs content is used in the composite. Otherwise, consolidation during sintering will be challenging [82,83]. For MMNCs with GNP content higher than 4 vol %, to reach full densification, an external pressure assisted method should be used.…”
Section: Consolidation and Sintering (Third Challenge)mentioning
confidence: 99%
“…It has to be mentioned that the residual porosity observed on the specimens with 5 and 10 vol% after pre-treatment ( Figure 7 d,e) also affects the electrical conductivity of these materials and, therefore, the anodizing process. Moreover, Srivastava et al [ 36 ] and Padmavathi et al [ 37 ] found that the electrical conductivity of Al/SiC p decreases with the increase in the volume fraction of the SiC p , not only due to the addition of a phase with lower conductivity than the Al matrix, but also because when high volume fractions of reinforcement particles are present, reinforcement clusters and porosity are often observed to decrease the electrical conductivity of the composite material.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the alumina particles act as a barriers to the movement of grain boundaries and hence delay for the grain growth [36]. Padmavathi et al [22] states that up to 10 vol% of SiC reinforcement in 6711 Al alloy results uniform distribution of of SiC particles throughout the matrix, as the SiC percentage increases beyond 10 vol% resulted cluster formation. Upto optimum percentage of reinforcement into metallic matrix gives homogeneous microstructure.…”
Section: The Effect Of Particle Size On Microstructurementioning
confidence: 99%